2003
DOI: 10.1023/b:ejep.0000027356.71414.bd
|View full text |Cite
|
Sign up to set email alerts
|

Increased Prevalence of Depression, Smoking, Heavy Drinking and Use of Psycho-Active Drugs among Unemployed Men in France

Abstract: Unemployed men are found to have significantly higher prevalences of depression (RR: 2.6), smoking (RR: 1.5 for regular and 1.7 for heavy), heavy drinking (RR: 1.7) and consumption of psycho-active drugs (RR: 3.6) than the working population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
8

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 25 publications
3
33
0
8
Order By: Relevance
“…Also, the current study did not employ a structured clinical interview for DSM-IV Axis I diagnoses when recruiting participants from any group, but rather a semi-structured interview used on previous occasions (Hester et al, 2009;Nestor et al, 2010Nestor et al, , 2008Roberts et al, 2009). Despite the strong co-occurrence between lifetime prevalence of depression and smoking (Khlat et al, 2004;Kushnir et al, 2010), we observed no group differences in mood using the Beck Depression Inventory and when screening participants for self-reported personal and familial mental health history. Furthermore, we cannot disqualify the potential confound of nicotine withdrawal in smokers during the testing session.…”
Section: Limitationsmentioning
confidence: 73%
“…Also, the current study did not employ a structured clinical interview for DSM-IV Axis I diagnoses when recruiting participants from any group, but rather a semi-structured interview used on previous occasions (Hester et al, 2009;Nestor et al, 2010Nestor et al, , 2008Roberts et al, 2009). Despite the strong co-occurrence between lifetime prevalence of depression and smoking (Khlat et al, 2004;Kushnir et al, 2010), we observed no group differences in mood using the Beck Depression Inventory and when screening participants for self-reported personal and familial mental health history. Furthermore, we cannot disqualify the potential confound of nicotine withdrawal in smokers during the testing session.…”
Section: Limitationsmentioning
confidence: 73%
“…Stress and depression have long been recognized as risk factors for substance use (Conway et al, 1981;Elder et al, 2000;Holahan, Moos, Holahan, Cronkite, and Randall, 2003;Khlat, Sermet, and Le Pape, 2004;Torikka, Kaltiala-Heino, Rimpela, Rimpela, and Rantanen, 2001). Migration itself is stressful (He et al, 1991;Landale and Oropesa, 2001); the poor working and living conditions may augment the stress perceived by these rural-to-urban migrants, leading to elevated levels of depression and substance use (Conway et al, 1981;Elder et al, 2000;Holahan et al, 2003;Khlat et al, 2004;Torikka et al, 2001;VanGeest and Johnson, 1997). The income of these migrants, although limited in most cases, may still be sufficient to allow access to substances.…”
Section: Rural-to-urban Migrants Are At An Increased Risk For Substanmentioning
confidence: 99%
“…Population-based surveys report that ethnic minorities contemplating cessation are less likely to seek help [66], due possibly to the lack of culturally appropriate programmes, and when programmes are adapted for specific groups post-intervention abstinence rates are higher [66,67]. Research conducted with prison inmates [68] and the unemployed [69,70] show similar patterns of high nicotine dependence, but high rates of motivation to quit, suggesting that such populations potentially stand to benefit the most from targeted smoking cessation treatments. For more information on smoking among high-risk groups, see the paper by Baker et al [71] in this Special Issue.…”
Section: Need For Greater Consideration Of Special Groupsmentioning
confidence: 99%